Kaj usmerja razvoj arhitekturne tehnologije - Kresal, Janez (AR. Arhitektura, raziskave, 2004)
The article analyses rules that direct development of architectural technology. They originate from three fields (economic, symbolic and utility values) that aren't in mutual hierarchical relations. They are economics, consumerism and innovativeness and have always been directing human civilisation. On the technological level these rules have been given understandable names: decreasing mass of elements, shortening production time, lowering maintenance costs, using low-energy technologies, shortening time of use, increasing choice of elements, and globalised technology. These phenomena answer the question: what directs development of architectural technology.
Keywords: architecture; arhitektura; technology; tehnologija; ekonomika; inovativnost